(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Recently, electrospun nanofiber membranes (ENMs) have been received an increased attention in personal protective clothing owing to their excellent filtration efficiency and low basis weight as filtering materials. However, high resistance to air flow is a major drawback of ENMs which in turn effect on comfort. In addition, comfort properties such as moisture management of ENMs need to be evaluated for practical applications. It is argued that air permeability and moisture management influenced by selection of electrospinning process parameters. This research studied the effect of collector speed and deposition time on the air permeability of ENMs. Polyacrylonitrile nanofibers that had the diameter in the range of 291–877 nm were fabricated. The deposition time significantly influenced air permeability, unlike collector speed. Hence a short deposition time is desirable. A good correlation was found between the theoretical porosity and experimental air permeability of ENM. Furthermore, it was found that moisture management properties of ENM require improvements for personal protective clothing.